Architectural Identity and the Portable Building - Robert Kronenburg (Oz, 1994)
The sense of identity associated with a specific place is intimately linked with the human consciousness. Heidegger states that; " ... 'place' places man in such a way that it reveals the external bonds of his existence and at the same time the depths of his freedom and reality."